Longer sleep durations are positively associated with finishing place during a national multiday netball competition - Juliff, L. E.; Halson, S. L.; Hebert, J. J.; Forsyth, P. L.; Peiffer, J. J. (The Journal of Strength and Conditioning Research, 2018)
Sleep is often regarded as the single best recovery strategy available to an athlete, yet little is known about the quality and quantity of sleep in athletes during multiday competitions. This study objectively evaluated sleep characteristics of athletes during a national netball tournament. Using wrist actigraphy monitors and sleep diaries, 42 netballers from 4 state teams were monitored for the duration of a tournament (6 days) and 12 days before in home environments. Significant differences were found between teams based on final competition standings, suggesting enhanced sleep characteristics in athlete's whose team finished higher in the tournament standings. The top 2 placed teams when compared with the lower 2 placed teams slept longer (8:02 ± 36:43; 7:01 ± 27:33), had greater time in bed (9:03 ± 0:52; 7:59 ± 0:54) and reported enhanced subjective sleep ratings (2.6 ± 0.5; 2.3 ± 0.6). Sleep efficiency was no different between teams. A strong correlation (r = -0.68) was found indicating longer sleep durations during competition were associated with higher final tournament positions. Encouraging athletes to aim for longer sleep durations in competition, where possible, may influence the outcome in tournament style competitions.